Implementation of Ruqyah as an Alternative to Islamic Medicine in Indonesia - Ratnasari, Kartika; Natasya, Cindy; Agustin, Yasmin Erly; Suprastiyo, Rahmad; Azzuhri, Zulfa Erfania; Amiruddin, Muhammad (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v2i0.2126, 2022)
One of the religious therapies in the life of Muslims is ruqyah. Ruqyah is a prayer accompanied by dhikr to Allah Almighty by reciting the holy verses of the Quran and hadith. Ruqyah is used to cure mental disorders, physical illnesses, and other conditions. This study aims to learn more about ruqyah in Islam, which is used as an alternative treatment. The method used to prepare this article is a literature study from national and international scientific journals. The study results in a show that ruqyah can be done if it does not contain elements of shirk and is recommended as a treatment because the reading of ruqyah contained verses of the Qur'an as a cure for all diseases.